2007
DOI: 10.1126/science.1147555
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genomic Data Identify the Closest Living Relative of Primates

Abstract: Infornnation about obtaining reprints of this article or about obtaining permission to reproduce this article in whole or in part can be found at: http://www.sciencennag.org/about/permissions.dtlScience (print ISSN 0036-8075; online ISSN 1095-9203) is published weekly, except the last week in December, by the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
226
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(241 citation statements)
references
References 25 publications
11
226
3
1
Order By: Relevance
“…S2). This result helped to clarify potential controversy regarding the phylogenetic position of tree shrew within eutherian mammals reconstructed on the basis of mitochondrial DNA genome 11 , genome-wide comparative chromosome map 10 and multilocus nuclear sequences 12,13 . It should be mentioned that we observed an unexpected deep split between our tree shrew and the one sequenced by the Broad Institute ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…S2). This result helped to clarify potential controversy regarding the phylogenetic position of tree shrew within eutherian mammals reconstructed on the basis of mitochondrial DNA genome 11 , genome-wide comparative chromosome map 10 and multilocus nuclear sequences 12,13 . It should be mentioned that we observed an unexpected deep split between our tree shrew and the one sequenced by the Broad Institute ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Analyses of the mitochondrial genome showed that the tree shrew had a closer relationship to Lagomorpha than to Dermoptera or primates, 11 and molecular cytogenetic data supported a Scandentia-Dermoptera sister clade 10 . However, available evidence from multiple nuclear genes suggests a closer affinity of tree shrews and primates (including human) 12,13 . In a recent study by Hallström et al 14 based on 3,000 genes for phylogenetic analysis, tree shrew was grouped with Glires (including Rodentia and Lagomorpha), suggesting a closer affinity of tree shrew with mouse or rabbits.…”
Section: Resultsmentioning
confidence: 99%
“…All molecularly based estimates for primate origins fall in the late Cretaceous (83.3-70.6 Ma) and those for the haplorhine-strepsirrhine split and anthropoid-tarsier split are older than ∼56 Ma (115)(116)(117)(118). In contrast, the oldest known fossil evidence for a "primate of modern aspect" is early Eocene (∼55.8 Ma) or late Paleocene if Altiatlasius is a euprimate.…”
Section: Biogeographymentioning
confidence: 98%
“…He interpreted the enlargement as a derived haplorhine feature. Other pieces of evidence suggesting that a reduced ICA is primitive for Euprimates include 1) the frequent reduction in this canal exhibited by plesiadapiform stemprimates (Gingerich, 1976;MacPhee et al, 1983;Kay et al, 1992;Boyer et al, 2012) and 2) the reduction exhibited by cynocephalid dermopterans (Table 1) (Wible, 1993) that some analyses suggest are more closely related to Euprimates than are treeshrews (Beard, 1993;Bloch et al, 2007;Janecka et al, 2007;O'Leary et al, 2013).…”
Section: What Was the Pattern Of Ica Evolution In Early Primates?mentioning
confidence: 99%